KERAGAMAN JENIS MAKROZOOBENTOS PADA AREAL MANGROVE REHABILITASI DAN ALAMI DISTRIK BIAK TIMUR KABUAPTEN BIAK NUMFOR: - - sinery, anton; Magdalena, Octovyanti; Purba, Gandi; Kaber, Yuanike (Median : Jurnal Ilmu Ilmu Eksakta, 2024)
Yenusi Village and Ruar, Biak Timur District, Biak Numfor Regency, respectively represent the mangrove rehabilitation caused by the 1996 tsunami by the Environmental Agency of Biak Numfor Regency in 2014 and the natural mangroves in this area. The success of rehabilitation activities can be seen not only from the presence of mangrove species but also through water biota. The aim of the research is to determine the diversity of macrozoobenthos biota in Yenusi Village as a representation of rehabilitated mangroves and Ruar Village as a representation of natural mangroves in the East Biak District, Biak Numfor Regency. Based on the results of the analysis, it is known that there are 43 types of macrozoobenthos from 4 classes, 21 families with a total of 3,263 individuals which include 34 types of snail groups (Gastropoda), 5 types of shellfish groups (Bivalvia), 2 types of shrimp groups (Crustacea), 2 types of groups of marine worms (Polychaeta) with species diversity index values ​​in these two mangrove areas of 2.61 (Ruar village) and 2.99 (Yenusi village) with the criteria "medium. 74.2% of macrozobenthic individuals were found in the mangrove area of ​​Yenusi village and the remaining 25.8% were found in the mangroves of Ruar village which shows that there is quite good adaptation of the species considering that the presence of macrozobenthic species and individuals in the mangrove rehabilitation area (Kampung Ruar) is much higher than natural habitat (Yenusi Village)